Group has Latin Square Property/Proof 1

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $\struct {G, \circ}$ be a group.

Then $G$ satisfies the Latin square property.

That is, for all $a, b \in G$, there exists a unique $g \in G$ such that $a \circ g = b$.

Similarly, there exists a unique $h \in G$ such that $h \circ a = b$.


Proof

\(\displaystyle g\) \(=\) \(\displaystyle a^{-1} \circ b\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle a \circ g\) \(=\) \(\displaystyle a \circ \paren {a^{-1} \circ b}\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle a \circ g\) \(=\) \(\displaystyle \paren {a \circ a^{-1} } \circ b\) Group Axiom $\text G 1$: Associativity
\(\displaystyle \leadsto \ \ \) \(\displaystyle a \circ g\) \(=\) \(\displaystyle e \circ b\) Group Axiom $\text G 3$: Existence of Inverse Element
\(\displaystyle \leadsto \ \ \) \(\displaystyle a \circ g\) \(=\) \(\displaystyle b\) Group Axiom $\text G 2$: Existence of Identity Element

Thus, such a $g$ exists.


Suppose $g, g' \in G$ where $a \circ g = b = a \circ g'$.

Then:

\(\displaystyle g\) \(=\) \(\displaystyle e \circ g\) Group Axiom $\text G 2$: Existence of Identity Element
\(\displaystyle \) \(=\) \(\displaystyle \paren {a^{-1} \circ a} \circ g\) Group Axiom $\text G 3$: Existence of Inverse Element
\(\displaystyle \) \(=\) \(\displaystyle a^{-1} \circ \paren {a \circ g}\) Group Axiom $\text G 1$: Associativity
\(\displaystyle \) \(=\) \(\displaystyle a^{-1} \circ b\) Substitution for $a \circ g$
\(\displaystyle \) \(=\) \(\displaystyle a^{-1} \circ \paren {a \circ g'}\) Substitution for $a \circ g'$
\(\displaystyle \) \(=\) \(\displaystyle \paren {a^{-1} \circ a} \circ g'\) Group Axiom $\text G 1$: Associativity
\(\displaystyle \) \(=\) \(\displaystyle e \circ g'\) Group Axiom $\text G 3$: Existence of Inverse Element
\(\displaystyle \) \(=\) \(\displaystyle g'\) Group Axiom $\text G 2$: Existence of Identity Element

Thus uniqueness holds.


To prove the second part of the theorem, let $h = b \circ a^{-1}$.

The remainder of the proof follows a similar procedure to the above.

$\blacksquare$


Sources